2022
DOI: 10.1136/jnnp-2022-330100
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 omicron breakthrough infections in patients with multiple sclerosis

Abstract: BackgroundIt is unclear which patients with multiple sclerosis (MS) are most susceptible for omicron breakthrough infections.MethodsWe assessed omicron breakthrough infections in vaccinated patients with MS with and without disease-modifying therapies enrolled in an ongoing large prospective study. We longitudinally studied humoral responses after primary and booster vaccinations and breakthrough infections.ResultsOmicron breakthrough infections were reported in 110/312 (36%) patients with MS, and in 105/110 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A recent study by Novak et al [27] found that 59% of patients on anti‐CD20 developed breakthrough non‐severe COVID‐19 after three injections of SARS‐CoV‐2 mRNA vaccine. Another study by van Kempen et al [28] found that patients on anti‐CD20 and S1PRM had a higher breakthrough COVID‐19 rate compared to patients on other treatments, but most infections were mild.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Novak et al [27] found that 59% of patients on anti‐CD20 developed breakthrough non‐severe COVID‐19 after three injections of SARS‐CoV‐2 mRNA vaccine. Another study by van Kempen et al [28] found that patients on anti‐CD20 and S1PRM had a higher breakthrough COVID‐19 rate compared to patients on other treatments, but most infections were mild.…”
Section: Discussionmentioning
confidence: 99%
“…Both responses were generally higher in patients who had a COVID-19 infection in addition to their vaccinations, which is in line with other published data in anti-CD20-treated patients as well as in the general population [ 11 , 25 , 33 , 34 , 35 ]. However, a few studies did not report a difference in antibody levels upon combined infection and vaccination [ 36 , 37 ]. In particular, hybrid immunity has been noted for its prominent effect on neutralizing SARS-CoV-2-specific antibodies, both in terms of their quantity and their neutralizing capacity with regard to a broad spectrum of variants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 However, these studies did not measure serology in all participants, instead focussing on clinical infection. Lack of seroconversion after initial vaccination, especially in the context of anti-CD20 and S1P treatments, has been reported to be associated with increased rates of COVID-19 by some, [11][12][13][14] but not all, 15 groups. The differential protective effect of vaccination against severe infections in those exposed to DMT associated with lower seroconversion is less clear, given the relative rarity of severe infection in the post-vaccination era.…”
Section: Risk Of Covid-19 In People With Multiple Sclerosis Who Are S...mentioning
confidence: 99%